As estratégias brasileiras de integração regional : os casos do Projeto SIPAM/ SIVAM na tríplice fronteira Brasil, Venezuela e Guiana (2000-2012) - Schwaizer, Vanessa Raskopf (2016)
This paper´s purpose is to study the Brazilian strategies of regional integration, aiming to develop the Pan-Amazonian region in a sustainable way, increasing the studies of SIVAM/SIPAM Project and the understanding of its importance to the sustainable development of the triple border area of Roraima, Venezuela and Guyana from 2000 to 2012. The Amazonian states have common interests and problems and its integration creates a specific multilateral strategy to find solutions to those matters. The Pan-Amazonian integration is necessary for the sustainable development of the region. The Brazilian search for regional integration is linked to the new security agenda that includes matters such as the fight against drugs and the preservation of the environment. These are the Brazilian political hot topics in the Amazonian locus, in the 21st century, and one of these political measures was the creation, in 2002, of the military project SIVAM – System of Surveillance of Amazonian, that later was inserted into SIPAM – System of Protection of Amazon. As an integration strategy, the SIVAM/SIPAM Program can be very important to the political strengthening and the sustainable development of the Pan-Amazonian states and the triple border region of Roraima, Venezuela and Guyana since it supplies data that can be used to the elaboration of policies between states of the region that will enhance the interaction between the social forces capable of using such richness of resources of regional biodiversity without destroying them, allowing the technical-scientific and cultural exchange, and contributing to the expansion of rights and capacities of the populations, of their freedom. To carry out this qualitative research, it was used the method of dialectic approach; having as procedure methods the methods of historical and of case study. The research techniques used were the indirect documentation and direct documentation. The SIVAM/SIPAM does not plan and does not take political measures in the Amazonian states, nor in the triple border region in here studied. Their contribution was and is to inform, supply mechanisms, technological infrastructure, providing a variety of possibilities for planning and action directed to the decision-makers and managers in the state of Roraima and the bordering countries.